2023
DOI: 10.1111/gfs.12608
|View full text |Cite
|
Sign up to set email alerts
|

The defoliation dynamics of a stockpiled native grassland pasture follow similar patterns between supplemented and unsupplemented beef calves

Abstract: It is unclear to what extent and on which variables does supplementing beef cattle on native grasslands affect sward structure, specifically on the dynamics of its grazing horizons. Three hypotheses were tested: (i) during a grazing down process under similar forage allowance, supplemented animals take longer to finish each grazing stratum, than their unsupplemented counterparts, (ii) in both cases, the upper stratum will be heavily depleted before the subsequent strata are grazed, (iii) some species and/or fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…It was possible to observe different phases over time (Figure 2), in which all experiments presented at least one phase in which the BW change over time of C and S animals behaved oppositely, where S animals were actively gaining BW while C animals were maintaining or losing BW. In a grazing-down experiment, Cazzuli et al [30] could not find any differences between S and C animals concerning change in green content over time of their swards nor on their plant functional types' species preferences. This suggests that the differences in BW change between C and S animals in this work-especially of C animals' BW change-may be only partially explained by herbage quality or species composition of the sward throughout the duration of the trials.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It was possible to observe different phases over time (Figure 2), in which all experiments presented at least one phase in which the BW change over time of C and S animals behaved oppositely, where S animals were actively gaining BW while C animals were maintaining or losing BW. In a grazing-down experiment, Cazzuli et al [30] could not find any differences between S and C animals concerning change in green content over time of their swards nor on their plant functional types' species preferences. This suggests that the differences in BW change between C and S animals in this work-especially of C animals' BW change-may be only partially explained by herbage quality or species composition of the sward throughout the duration of the trials.…”
Section: Discussionmentioning
confidence: 89%
“…The top leafy stratum of pastures is expected to be preferred among all other pasture components [37], meaning that it would be consumed before the rest of the sward, and therefore, the green leaf content would be expected to decline throughout trials. Even though Cazzuli et al [30] found an opposite trend-at least at the end of a long stockpiling period and before grazing activities began-Benvenutti et al [37] found that the fCP content of a C4 species dominated sward was greater in the upper stratum of the sward. Should the latter be the case, during the final phases, the pastures would be offering lower quality forage in terms of fCP, which matches our results because, during this late stage, the lower the fCP, the greater the response.…”
Section: Discussionmentioning
confidence: 98%